Implementation of Green Accounting to Increase Awareness Environment and Knowledge in East Cirebon Region (Case Study of Beverage MSME Business Actor) - Setia Wati; Trishe Silinia Arafah; Rochanda Wiradinata; Nurul Senja (Greenation Research & Yayasan Global Resarch National, 2024)
The negative impacts of global warming and climate change increase the need for environmental improvement efforts. Green accounting in the East Cirebon region is considered to have strategic potential to increase environmental awareness and public knowledge of environmental issues. Green accounting includes an approach that incorporates ecological values into the traditional accounting system to provide a comprehensive understanding of the impact of the economy on the environment. The purpose of this study was to determine the impact of the application of green accounting on increasing environmental awareness and public knowledge in the East Cirebon region. This research uses a qualitative approach with descriptive qualitative methods through in-depth interviews, observations, surveys, and distributing questionnaires to small and medium enterprises. The results showed that the application of green accounting in the East Cirebon region had a positive impact on increasing environmental awareness. By presenting accounting information that considers the environment, people can understand the economic impact of their activities on local ecosystems. In addition, increased environmental awareness will lead to active participation in conservation programs and raise awareness of the importance of sustainability. Applying green accounting also helps increase community knowledge and support sustainable conservation efforts in the East Cirebon region. This study concludes that applying green accounting in the East Cirebon region can positively contribute to increasing environmental awareness and community knowledge. Therefore, local governments, businesses, and communities should work together to continue and expand the application of green accounting to achieve sustainable regional development.